Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1175/jamc-d-22-0122.1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Urban Blending in Homogenized Temperature Records in Japan and in the United States: Implications for the Reliability of Global Land Surface Air Temperature Data

Abstract: In order to reduce the amount of non-climatic biases of air temperature in each weather station’s record by comparing it to neighboring stations, global land surface air temperature datasets are routinely adjusted using statistical homogenization to minimize such biases. However, homogenization can unintentionally introduce new non-climatic biases due to an often-overlooked statistical problem known as “urban blending” or “aliasing of trend biases”. This issue arises when the homogenization process inadvertent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…Meanwhile, the urban and rural ST implies 60% more warming than the rural-only ST (0.885°C/100y compared to 0.554°C/100y) and even more warming than any of the other ST estimates (also already noted by C2021). This is consistent with other studies that have argued that the land component of current global temperature estimates remains significantly contaminated by urbanization biases, e.g., Soon et al (2015), Zhang et al (2021), Scafetta (2021), Katata et al (2023).…”
Section: Resultssupporting
confidence: 92%
“…Meanwhile, the urban and rural ST implies 60% more warming than the rural-only ST (0.885°C/100y compared to 0.554°C/100y) and even more warming than any of the other ST estimates (also already noted by C2021). This is consistent with other studies that have argued that the land component of current global temperature estimates remains significantly contaminated by urbanization biases, e.g., Soon et al (2015), Zhang et al (2021), Scafetta (2021), Katata et al (2023).…”
Section: Resultssupporting
confidence: 92%
“…AR6 has explicitly argued that urbanization bias represents less than 10% of the longterm warming, but several recent studies have disputed this claim [5,7,9,10,78]. Meanwhile, AR6 argues that the Matthes et al (2017) solar forcing dataset has been confirmed to be reliable, yet this claim is challenged by several studies arguing it has not yet been satisfactorily resolved which (if any) of the many solar forcing datasets are most reliable [5,7,12,15].…”
Section: Discussionmentioning
confidence: 99%
“…However, we caution that the current approaches of using statistical homogenization techniques to correct temperature records for non-climatic biases are prone to "aliasing effects" [74,75], including "urban blending" [5,76,77]. Katata et al (2023) have offered some potential modifications to temperature homogenization to reduce or remove this problem [78].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation